2014
DOI: 10.1007/s00247-014-3248-x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging evaluation of fetal vascular anomalies

Abstract: Vascular anomalies can be detected in utero and should be considered in the setting of solid, mixed or cystic lesions in the fetus. Evaluation of the gray-scale and color Doppler US and MRI characteristics can guide diagnosis. We present a case-based pictorial essay to illustrate the prenatal imaging characteristics in 11 pregnancies with vascular malformations (5 lymphatic malformations, 2 Klippel-Trenaunay syndrome, 1 venous-lymphatic malformation, 1 Parkes-Weber syndrome) and vascular tumors (1 congenital h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Clinical features of KTS within right lower extremity in our patient: limb hypertrophy, port wine stain, phlebolymphedema, large varicose veins and skin lesions secondary to venous and lymphatic insufficiency; A -front view; B -side view; C -back viewA B C DiscussionKTS in the literature is known by various names, including angioosteohypertrophy syndrome or capillary-lymphaticovenous malformation[3,10,11]. The first case was reported in 1900 by Maurice Klippel and Paul Trenaunay[12]…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Clinical features of KTS within right lower extremity in our patient: limb hypertrophy, port wine stain, phlebolymphedema, large varicose veins and skin lesions secondary to venous and lymphatic insufficiency; A -front view; B -side view; C -back viewA B C DiscussionKTS in the literature is known by various names, including angioosteohypertrophy syndrome or capillary-lymphaticovenous malformation[3,10,11]. The first case was reported in 1900 by Maurice Klippel and Paul Trenaunay[12]…”
mentioning
confidence: 67%
“…The aetiology of the syndrome remains unknown and many theories have been proposed. It is generally accepted that KTS is a congenital disorder, in which blood and lymph vessels do not properly form during intrauterine development [11,[14][15][16]. KTS is postulated to be the result of sporadic mutations, including chromosomal translocations such as: t(5;11) (q13.3;p15.1) [17,18] or t(8;14)(q22.3;q13) [19], supernumerary ringed chromosome 18 [20], mutations in the PIK3CA gene [21], and somatic mutations in RASA 1 gene [22][23][24].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal MRI is usually performed for further evaluation of a facial or cervical mass detected on routine obstetric US. The suggested MRI protocol for imaging of the fetal face and neck includes the following sequences 11,59 : (a) Half‐Fourier acquisition single‐shot turbo (HASTE), which provides heavily T2 weighted imaging with low susceptibility within a very short time. It is excellent for visualization of normal anatomical structures and depiction of lesion morphology; (b) Spoiled gradient echo T1‐weighted sequence for imaging of the thyroid gland and major cervical vessels as well as for depiction of intralesional blood products; (c) Gradient echo planar imaging for the detection of blood products, calcification, and bony details; (d) Dynamic steady state or balanced gradient echo sequences, which are valuable for assessment of the swallowing function of the fetus (Figure 9).…”
Section: Fetal Face and Neck Tumorsmentioning
confidence: 99%
“…Histologically, KHE is composed of solid nodules that are a mixture of spindle-shaped endothelial cells and small capillary vessels. The typical magnetic resonance imaging (MRI) presentation of KHE is homogeneous hyperintense in T2-weighted sequences and isointense in T1-weighted sequences4. Numerous studies have revealed an exclusive relationship between KHE and Kasabach-Merritt Phenomenon (KMP), which is characterized by consumptive coagulopathy and thrombocytopenia with enlarging vascular tumors, including KHE and tufted angioma (TA)5.…”
mentioning
confidence: 99%